Shaw and Joyce : the last word in stolentelling - Black, Martha Fodaski (Florida James Joyce series., 1995)
This controversial and groundbreaking book - certain to provoke Joyce scholars - documents the heretofore under observed influence of George Bernard Shaw on James Joyce. In painstaking detail, Martha Fodaski Black addresses Joyce's "stolentelling" from Shaw, maintaining that Joyce employed literary ruses to obscure the relationship between himself and his Irish predecessor - stratagems that argue for Joyce's own originality. Shaw and Joyce were both literary pickpockets, like most writers, but Shaw (unlike Joyce) readily admitted his sources. Black seeks "to restore Shaw's reputation, to prove that the crafty Joyce secretly approved of and used the old leprechaun playwright, and to quarrel with critics who isolate texts from the faces behind them."